Josip Plemelj in pravilni sedemkotnik - Hladnik, Milan (Obzornik za matematiko in fiziko, 2013)
Plemelj's approach to the construction of (the side of) the reghular heptagon requires some preliminary mathematical explanation. Also a slight addition and two recent variations of Plemelj's idea are given.
Keywords: geometrijske konstrukcije; evklidsko orodje; pravilni sedemkotnik; Gleasonova konstrukcija; Conwayeva konstrukcija